Sensitivity of the Southern Ocean to enhanced regional Antarctic ice sheet meltwater input. Issue 10 (17th November 2015) - Fogwill, C. J.; Phipps, S. J.; Turney, C. S. M.; Golledge, N. R.
Abstract: Despite advances in our understanding of the processes driving contemporary sea level rise, the stability of the Antarctic ice sheets and their contribution to sea level under projected future warming remains uncertain due to the influence of strong ice‐climate feedbacks. Disentangling these feedbacks is key to reducing uncertainty. Here we present a series of climate system model simulations that explore the potential effects of increased West Antarctic Ice Sheet (WAIS) meltwater flux on Southern Ocean dynamics. We project future changes driven by sectors of the WAIS, delivering spatially and temporally variable meltwater flux into the Amundsen, Ross, and Weddell embayments over future centuries. Focusing on the Amundsen Sea sector of the WAIS over the next 200 years, we demonstrate that the enhanced meltwater flux rapidly stratifies surface waters, resulting in a significant decrease in the rate of Antarctic Bottom Water (AABW) formation. This triggers rapid pervasive ocean warming (>1°C) at depth due to advection from the original site(s) of meltwater input. The greatest warming is predicted along sectors of the ice sheet that are highly sensitized to ocean forcing, creating a feedback loop that could enhance basal ice shelf melting and grounding line retreat. Given that we do not include the effects of rising CO2 —predicted to further reduce AABW formation—our experiments highlight the urgent need to develop a new generation of fully coupled ice sheet climate models, which include feedback mechanisms such as this, to reduce uncertainty in climate and sea level projections. Key Points: Antarctic Bottom Water formation rate highly sensitized to freshwater input Ocean stratification leads to reduced vertical mixing and warming at depth Warming occurs in sectors of Antarctic ice sheet sensitized to ocean forcing